2014
DOI: 10.1177/154431671403800201
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Lower-Extremity Venous Pulsatility is not always the Result of Cardiac Dysfunction

Abstract: Introduction The presence of peripheral venous pulsatility is widely recognized and commonly attributed to cardiac dysfunction; however, the precise cause(s) have been poorly defined in the literature. We have noted multiple patterns of venous pulsatility, often in patients with no history of heart disease. In a normal, high compliance venous system, cardiac pulsatility is continually dampened with distance from the heart. We theorized that in a low-compliance system, the pulsatility would be transmitted throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The position is important as gravity, and activity can alter those signals. 13 The examination of the CFV is started from the inguinal ligament. CFV examination can be obtained either in short axis without angle correction or in long axis with angle correction of less than 60° using pulsed wave Doppler (PWD) at 10-cm/s velocity scale.…”
Section: Discussionmentioning
confidence: 99%
“…The position is important as gravity, and activity can alter those signals. 13 The examination of the CFV is started from the inguinal ligament. CFV examination can be obtained either in short axis without angle correction or in long axis with angle correction of less than 60° using pulsed wave Doppler (PWD) at 10-cm/s velocity scale.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any extrinsic or intrinsic obstruction of the inferior vena cava, such as a stenosis after liver transplant ( 55 ), will alter the CFV Doppler signal. In a cohort of 30 healthy subjects, Schroedter et al ( 56 ) observed CFV pulsatility when patients were submitted to change in position and exercise. However, there were no measurements of right atrial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler echocardiography is currently considered to be the most valuable and definitive tool in the assessment of different heart diseases including valvular regurgitation, and its sensitivity and specificity are comparable to cineangiography ( 27 ) . A literature review shows that Doppler echocardiography is more sensitive than cardiac auscultation, particularly in cases where valvular regurgitation is mild ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%